Menneskeretligt lys på resocialisering i dansk straffuldbyrdelsesret - Hans Jørgen Engbo (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article seeks to clarify the concept of rehabilitation in the context of human rights and demonstrate its incorporation into applicable prison law in Denmark. The discussion begins with a summary of select US judgments and analyses of case law. It then delves into the most prominent stipulations and recommendations of international law. Finally, it proceeds to an analysis of the status of rehabilitation within Danish law. The article concludes that while Danish law concerning rehabilitation is generally in harmony with human rights requirements and recommendations, there are certain instances where legislation and practice fall short of human rights standards